Systematic Literature Review: Sistem Informasi Manajemen Inventory Barang Berbasis Web - Azriel Fachrul Rezy; Ines Heidiani Ikasari (Shofanah Media Berkah, 2023)
Web-based Goods Inventory Management Information System is an information system used to manage and control an organization's inventory through a web platform. A web-based inventory management information system provides easy access, scalability and flexibility in inventory management. This system stores and manages inventory data centrally, allowing real-time access to inventory information from various locations and devices connected to the internet network. The web-based goods inventory management information system can also be integrated with other systems such as financial systems, marketing systems, and e-commerce platforms. The research method used in this study is systematization and analysis of relevant literature found from various academic and professional sources. This study identifies and categorizes research related to web-based inventory management information systems based on topics, research methods, and results achieved. In conclusion, this study provides a comprehensive understanding of web-based inventory management information systems, including concepts, methods, technologies, and benefits. This literature review can be the basis for the successful development and implementation of a web-based inventory management information system in various organizations.